Early stages of ZIF-8 film growth: the enhancement effect of primers exposing sulfonate groups as surface-confined nucleation agents - Tuninetti, Jimena Soledad (2015)
We describe the use of sulfonate-terminated self-assembled monolayers as very efficient surface-confined nucleation agents for rapid growth of dense, thick and well-percolated ZIF-8 films.